Nanoemulsions of Biosurfactant and Cinnamon Essential Oil: A Promising Antimicrobial Approach for Oral Pathogens - Isty Adhitya Purwasena; Anriansyah Renggaman; Dzulianur Mutsla; Nurul Wahyuni; Annisa Afiva; Dea Ajeng Pratiwi (3BIO: Journal of Biological Science, Technology and Management, 2026)
Dental and oral care products often contain Sodium Lauryl Sulfate (SLS), which can cause allergic reactions and mucosal infection. Biosurfactants (BS) and cinnamon essential oil (CEO) are safer alternatives due to their antimicrobial properties. This study screens BS form five bacterial isolates, CEO, and their nanoemulsions prepared by low-energy method (NEL) and high- energy method (NEH) for inhibiting oral pathogens. Results showed that BS from Bacillus altitudinis were most effective against Candida albicans, while BS from Bacillus siamensis were most effective against Streptococcus mutans and Enterococcus faecalis. The minimum concentrations of CEO inhibiting C. albicans were 1900 ppm and both S. mutans and E. faecalis were 490 ppm. The minimum NEL and NEH concentration inhibiting C. albicans was 3.125 ppm BS+ 175 ppm CEO and 6.25 ppm BS + 350 ppm CEO, respectively. The minimum NEL concentration inhibiting S. mutans and E. faecalis was 7.82 ppm BS + 120 ppm CEO and 1.95 ppm BS + 120 ppm CEO, while the minimum concentration of both NEH was 3.125 ppm BS+ 175 ppm CEO. These findings suggest that BS combined with CEO in nanoemulsions are effective in inhibiting oral pathogens and can serve as promising alternatives to SLS.